An Introduction to Pathology in Biomedical Research: A Mission-Critical Specialty for Reproducibility and Rigor in Translational Research. (22nd July 2019) - Brayton, Cory F; Boyd, Kelli L; Everitt, Jeffrey L; Meyerholz, David K; Treuting, Piper M; Bolon, Brad
Abstract: This issue of ILAR Journal focusses on pathology and pathologists in biomedical research, more specifically in preclinical translational research involving (nonhuman) animals, emphasizing academic settings. Considerations in study design and planning to maximize benefit from pathologists and pathology resources are reviewed. Adjunctive technologies including molecular techniques, digital pathology, and imaging are highlighted. Additional considerations regarding safety and regulatory concerns, and veterinary clinical trials are reviewed as well. Pathology has been fundamental to understanding clinical disease, remains fundamental to diagnosing disease, and is required in drug and device development. Broader integration of pathology expertise and well-designed pathology investigations have much to offer research rigor and reproducibility, and successful translation from biomedical research.